Antoine de Saint Exupery: uma análise das escolhas simbólicas na obra O pequeno príncipe - Muller, Caroline Appel (2017)
This work is the result of a study on how a life of Antoine de Saint-Exupéry influenced the symbolic choices within the work The Little Prince, in view of the historical context in which it was created. A relationship between a life experience of the author and his representative characters is verified, thus verifying their significations. The work The Little Prince was published in 1943, and had and still has worldwide repercussion for being the third best selling book in the history of the classics. Known for being a work of children's literature, its vast content and richness of "moral lessons" turns out to be a reading directed also for adults. Antoine impresses his readers with his work that speaks of themes such as love, his intention, gratitude, among others, even though it was written in a turbulent period of his life, when he was exiled in the United States in the period of World War II. An analysis constituted through the bibliographic study, through the collection of data in books and articles. And it is through the contextualization of the work The Little Prince, describing a relation author and work, identifying the symbolic elements through the author, through a summary of what is semiotic, that comes to a conclusion on how symbolic images as characters Little Prince, The Rose and the Volcanoes. In this way it was possible to conclude that life and as experiences of the author, certainly, is part and influenced as imagistic representations of the work cited.